Clinicopathological study of thyroid swellings - Gupta, Anchal; Jamwal, Padam Singh (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Diseases of the thyroid continue to be a common clinical problem having a prevalence rate of 4 to 7% in the general population. Methods: This retrospective study was conducted in the Department of ENT, Head and Neck Surgery, SMGS Hospital, Jammu from January 2018 to January 2020. A thorough history taking, meticulous clinical examination, routine hematological and biochemical investigations were done in all the patients. General examination of the patient was done and looked for thyroid functional abnormality followed by local examination was carried out to locate and identify the site of the swelling, shape, size and consistency of the thyroid swelling and clinical diagnosis was made. All thyroid swelling cases were subjected to fine needle aspiration cytology (FNAC). The type of thyroidectomy is based on the size and type of thyroid whether neoplastic or non-neoplastic. All the specimens were sent for histopathological examination. Results: Out of 60 patients in the study, 56 were females and only 4 were males. The most common age group was 31 to 40 years seen in 24 (40%) patients. The most common presenting symptom was swelling in the neck seen in 58 (96.67%) patients. The most common diagnosis on FNAC was colloid goiter seen in 40 (66.67%) patients. The most common was benign nodular colloid goiter seen in 35 (58.33%) patients. Conclusions: Fine needle aspiration is a very useful and indispensible test in the diagnosis of thyroid lesions.